Additive manufacturing of titanium alloy could modify the pathogenic microbial profile: an in vitro study - PINGUEIRO,João (2019)
Abstract Additive manufacturing (AM) is an emerging process for biomaterials and medical devices. Direct Laser Metal Sintering (DLMS) is an AM technique used to fabricate Ti–6Al–4V implant materials with enhanced surface-related properties compared with wrought samples; thus, this technique could influence microbial adsorption and colonization. Therefore, this in vitro study was conducted to evaluate the impact of different implant production processes on microbial adhesion of periodontal pathogens. Titanium discs produced using two different processes—conventional and AM—were divided into three groups: conventional titanium discs with machined surface (G1), AM titanium discs with chemical treatment (G2) and AM titanium discs without chemical treatment (G3). Subgingival biofilm composed of 32 species was formed on the titanium discs, and positioned vertically in 96-well plates, for 7 days. The proportions of microbial complexes and the microbial profiles were analyzed using a DNA–DNA hybridization technique, and data were evaluated using Kruskal–Wallis and Dunnett tests (p < 0.05). Lower proportions of the red complex species were observed in the biofilm formed in G2 compared with that in G1 (p < 0.05). Moreover, the proportions of the microbial complexes were similar between G2 and G3 (p > 0.05). Compared with G1, G2 showed reduced levels of Porphyromonas gingvalis , Actinomyces gerencseriae, and Streptococcus intermedius , and increased levels of Parvimonas micra , Actinomyces odontolyticus, and Eikenella corrodens (p < 0.05). The microbial profile of G3 did not differ from G1 and G2 (p > 0.05). The results of this in vitro study showed that titanium discs produced via AM could alter the microbial profile of the biofilm formed around them. Further clinical studies should be conducted to confirm these findings.